The Role of Japanese Candlesticks in Analyzing the Price Movement of the Saudi General Index during the Period (2021-2018) - Souad Aounallah, Asma Bentrad, (European Economic Letters (EEL), 2024)
The aim of this study is to cover various aspects of technical analysis in general, with a focus on the pattern of Japanese candlesticks as a model for analyzing the price movement of financial market indices. This is done through the use of monthly data for the prices of the Saudi General Index and monitoring its developments during the period from 2021 to 2018. We concluded that Japanese candlestick charts are among the most accurate tools of technical analysis compared to other analytical tools. They are distinguished from other charting methods by the additional amount of information they provide to traders. Moreover, if read correctly, they can send a specific message that can be used as guidance and relied upon in forming a specific viewpoint regarding the analysis of price movements for financial market indices.